Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/ma13112574
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Homogenization and Solution Treatments Time on the Microstructure and Hardness of Inconel 718 Fabricated by Laser Powder Bed Fusion Process

Abstract: In the present study, Inconel 718 (IN718) superalloy fabricated by laser powder bed fusion (LPBF) has been characterized focusing on the effect of both homogenization and solution treatment time on grains structure, crystallographic texture, precipitates formation/dissolution and material hardness. For this purpose, a heat-treatment time window with a wide range of soaking times for both treatments was established aiming to develop the optimal post-treatment conditions for laser powder bed fused IN718. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 33 publications
6
22
0
Order By: Relevance
“…This is attributed to dramatic differences in the initial microstructure obtained after the LPBF, casting and forging manufacturing methods. In our previous study 24 , a post-heat treatment time window covering a wide range of soaking times for the homogenization (from 1 to 7 h at 1080 °C) and solution (from 15 to 60 min at 980 °C) treatments was established, and the effects of these post-treatment conditions on the microstructure, material texture, precipitates and hardness were studied. The objective of that study 24 was to tune the homogenization and solution treatment times to improve the microstructure of LPBF IN718 components, with the ultimate goal of optimizing their mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is attributed to dramatic differences in the initial microstructure obtained after the LPBF, casting and forging manufacturing methods. In our previous study 24 , a post-heat treatment time window covering a wide range of soaking times for the homogenization (from 1 to 7 h at 1080 °C) and solution (from 15 to 60 min at 980 °C) treatments was established, and the effects of these post-treatment conditions on the microstructure, material texture, precipitates and hardness were studied. The objective of that study 24 was to tune the homogenization and solution treatment times to improve the microstructure of LPBF IN718 components, with the ultimate goal of optimizing their mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study 24 , a post-heat treatment time window covering a wide range of soaking times for the homogenization (from 1 to 7 h at 1080 °C) and solution (from 15 to 60 min at 980 °C) treatments was established, and the effects of these post-treatment conditions on the microstructure, material texture, precipitates and hardness were studied. The objective of that study 24 was to tune the homogenization and solution treatment times to improve the microstructure of LPBF IN718 components, with the ultimate goal of optimizing their mechanical properties. It was found that after the homogenization treatment for 1 h at 1080 °C, Laves phases and elemental segregation formed during the printing process were not completely dissolved, and the as-printed texture and grain structure were not significantly affected 24 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations